Exercise in the setting of hematopoietic stem cell transplantation - Wiskemann, Joachim (European review of aging and physical activity, 2013)
The procedure of hematopoietic stem cell transplantation (HSCT) is an intense treatment approach to cure patients from leukemia or lymphoma. Prior, during, and after HSCT, patients experience considerable physical and psychosocial distress. In light of the increasing number of successfully treated patients, the need is growing for evidence-based adjuvant therapy options, which are able to reduce treatment-related side effects and enhance the rehabilitation process. Exercise constitutes to be a promising intervention in this setting due to its multidimensional effectiveness. The purpose of this article was to review the current knowledge in the field of exercise and HSCT. Therefore, an electronic literature search in PubMed on the topic was performed. Twenty-nine articles could be identified and classified as relevant for this paper. Reviewed studies suggest that exercise training is an important therapeutic approach in the supportive care for transplant patients. Significant benefits from the exercise interventions have been reported for physical performance, quality of life (QoL), and fatigue status. Several other benefits, such as a more rapid immune recovery or alleviation of therapy-related side effects have been reported in some studies. Future studies should address existing methodological problems, identify further effect levels of exercise and integrate a long-term perspective for the participants in the context of hematopoietic stem cell transplantation. Furthermore, potential biological pathways of exercise in HSCT patients should be investigated.
Gesehen am 18.11.2021